AC susceptibility and Mossbauer study of Ce3+ ion substituted SrFe12O19 nanohexaferrites. Issue 9 (15th June 2018) - Almessiere, M.A.; Slimani, Y.; Güngüneş, H.; El Sayed, H.S.; Baykal, A.
Abstract: Ce 3+ ion substituted SrFe12 O19, SrFe12 -x Cex O19 (0.0 ≤ x ≤ 0.5), nanohexaferrites were fabricated by citrate sol-gel combustion approach. X–ray diffractometry (XRD), Scanning electron microscopy (SEM), Energy dispersive spectroscope (EDX), EDX Elemental mapping, Fourier transform infrared spectroscopy (FT-IR) were used to study the structure and morphology of the samples. AC magnetic susceptibility and 57 Fe Mossbauer spectroscopy have been operated to examine the hyperfine structure, static and dynamic magnetic properties. The values of variations in line width, quadrupole splitting, hyperfine magnetic field, and isomer shift have been estimated. The impact of Ce-ion substitution on AC magnetic susceptibility properties of Sr-hexaferrite were explored. The AC-susceptibility measurements reveal the frequency dependence of the magnetic responses, indicating strong magnetic interactions among the nanoparticles of the various products. In addition, it is determined that the magnetic interaction between the nanoparticles is weakened in the substituted products, due to the substitution of Fe 3+ ions by Ce 3+ ions.